MEDIASI KONFLIK SEBAGAI SOLUSI TRANSFORMATIF UNTUK MENINGKATKAN IKLIM ORGANISASI DAN MUTU PENDIDIKAN - Arifin, Misbahul; Agus R, Abu Hasan (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2025)
This study examines the role of conflict mediation as a transformative approach to strengthening school organizational climate and improving educational quality. Using a literature review of 30 key scholarly sources, the study finds that conflicts within schools are not merely obstacles to progress but hold constructive potential when mediated effectively. Mediation fosters equal dialogue, interest alignment, and relationship restoration, enabling a shift from destructive to collaborative communication patterns. The findings indicate that well-implemented mediation processes enhance trust, psychological safety, and mutual respect within school communities—fundamental components of a healthy organizational climate. Such a climate contributes directly to increased teacher motivation and job satisfaction, improved instructional interactions, and the development of students’ socio-emotional skills, ultimately advancing educational quality in a sustainable manner. Although conceptual, this study makes a significant contribution by integrating conflict mediation, organizational climate, and educational quality into a coherent conceptual framework. The study recommends further empirical research to evaluate the measurable effectiveness of mediation programs in various school contexts as an organizational-based strategy for quality improvement.